TINJAUAN MAQASHID SYARI'AH TERHADAP AKAD NIKAH ONLINE - Murniati; Sholihah, Firda (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2024)
The validity of a marriage depends on fulfilling the terms and conditions of marriage. In the implementation of online marriage contracts, there are differences in the fulfillment of the pillars and conditions of the marriage, such as not gathering the bride and groom, the guardian of the marriage, and two witnesses in one place when the consent or marriage contract takes place, which has become a topic of discussion among ulama and legal experts. The reason is, there is still a lot of debate regarding this law. From the phenomenon of implementing online marriage contracts, questions arise regarding how online marriage contracts are carried out and how maqashid sharia reviews the implementation of online marriage contracts. This research aims to analyze how the online marriage contract is implemented and analyze the maqashid sharia review of the implementation of the online marriage contract. This research uses qualitative methods with the type of library research. The data collection technique used is documentation. From the results of this research, the author found that the implementation of the online marriage contract fulfilled the pillars and requirements of marriage. Apart from that, marriage contracts carried out online are also in accordance with maqashid sharia in terms of hifdz ad-din because it protects people from adultery which can damage honor, hifdz an-nafs because it protects the soul from things that threaten safety due to the Covid-19 pandemic and udzur one of the bride and groom, as well as hifdz an-nasl because marriage will produce offspring who can maintain continuity between generations. The implementation of an online marriage contract is legally permissible if it meets the pillars and requirements of marriage and meets the maqashid of sharia.